Code switching as the medium of solidarity in ‘Ola Bola’ - Marlyna Maros; Nur Diana Melissa Mohd Noorizan; Abd Hakim Ikram Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of the study is to investigate code switching (CS) exchanges in the movie Ola Bola; one of the highest box office movies in the Malaysian history in 2016, with a gross collection of the ticket selling of almost RM16 million (Finas, 2016). The study analysed the reasons why Malaysians; as aptly portrayed by the multi-racial characters in this particular movie, code switch in their daily interactions based on the theory proposed by David Crystal (1987). Another part of this study identified the types of code switchings used in this movie from the categories proposed by Shana Poplack (1980). Discussions from the findings show how the usage of code switchings depicts the spirit of solidarity, patriotism and unity in a multi-racial society; from Malaysian perspective.